THE INFLUENCE OF NATURAL IDEAS IN PROMOTING GENIUS LOCI (CASE STUDY OF SHEIKH LOTFOLLAH MOSQUE IN ISFAHAN) - Seirafian Baboldashti, Mahgol; Tabaeian, Seyedeh Marzieh; Shirvani Dastgerdi, Ahmadreza (Journal of Islamic Architecture, 2018)
Sheikh Lotfollah Mosque is one of the most beautiful and salient examples of Iranian architecture of the Safavid era, in Isfahan. Despite the scientific studies on the architecture of this mosque, its sacred and semantic concepts have been overlooked behind its hidden values. Therefore, the Sheikh Lotfollah Mosque has been studied as a human-made place using the phenomenological approach to architecture, in order to understand the importance of inducing the concept of genius loci; and by examining each of the elements and comparing them to the ideas and components of place. The authors try to answer the question that what environmental qualities of the Sheikh Lotfollah Mosque build its genius loci? The research method used in this paper was phenomenology and information were gathered by library studies. The result of the research indicates that this Mosque has significant values, including semantic load, and there is a relationship between its elements and their material and semantic qualities created by concepts such as enclosure, span, and space. Thus, this integrated logical system confers Sheikh Lotfollah Mosque a genius loci which has been a meaningful quality of this space throughout the centuries and continues to remind the future generations of Iranian cultural identity.